Karakterisasi Pati Canna Edulis Kerr. Termodifikasi dan Uji Produk pada Pembuatan Roti Tawar - siti munfarida; Jefri Pandu Hidayat (PERTETA, 2023)
Increasing population growth has an impact on increasing food demand, one of which is wheat flour. Increasing imports of wheat flour is not the solution. Canna tuber has high carbohydrate content. But it has a brownish color, low solubility and swelling power. The purpose of the study was to determine the optimum conditions to increase the quality of Canna starch by oxidation process using hydrogen peroxide (H2O2) as an alternative flour according to the quality standard of SNI 3751:2009. The research used white canna tubers as raw material to make canna starch. The starch was oxidized using H2O2 (1%, 2%, 3%) with variables slurry ratio of 10%, 20% and 30% within 30, 60, 90, and 120 minutes. The highest value of solubillity and swelling power was got at 60 minutes process and 10% slurry. The modification process is continued to find the optimum H2O2 concentration. The highest swelling power and solubility were obtained at 2% H2O2. The optimum condition is 10% slurry concentration, 2% H2O2 and 60 minutes oxidation time. The value of swelling power is 2.9 and water solubility is 0.0609. Proximate analysis was found 85.956% carbohydrates, 2.365% protein, 0% fat, 11.425% water and 0.254% ash. While the results of the white degree test show a brightness value of 91.95. Total protein did not reach the SNI standard, but modified canna starch can be used as substitute for wheat flour as much as 50% according to the test result of bread making application.